2020
DOI: 10.1109/access.2020.2990980
|View full text |Cite
|
Sign up to set email alerts
|

Building a Comprehensive Automated Programming Assessment System

Abstract: Automated Programming Assessment Systems (APAS) are used for overcoming problems associated with manually managed programming assignments, such as objective and efficient assessing in large classes and providing timely and helpful feedback. In this paper we survey the literature and software in this field and identify the set of necessary features that make APAS comprehensive -such that it can support all key stages in the assessment process. Put differently, comprehensive APAS is generic enough to meet the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In addition to assessing programming and functional programming, OJ systems have recently been used to assess complex exercise-based contents such as circuit design and AI [18]. In [39], an automated programming evaluation tool called Edgar was proposed and used to evaluate and analyze a variety of programming tasks. This system does not provide recommendations or any other type of personalized evaluation.…”
Section: Oj Systemsmentioning
confidence: 99%
“…In addition to assessing programming and functional programming, OJ systems have recently been used to assess complex exercise-based contents such as circuit design and AI [18]. In [39], an automated programming evaluation tool called Edgar was proposed and used to evaluate and analyze a variety of programming tasks. This system does not provide recommendations or any other type of personalized evaluation.…”
Section: Oj Systemsmentioning
confidence: 99%
“…This study showed that numerous useful hidden features can be extracted by analyzing the M2B system's data. Mekterović et al [12] proposed an APA system for conducting programming courses and created the educational software Edgar to automatically evaluate programming assignments and other programming-related tasks. Edgar provides a variety of services, including content writing, course administration, system monitoring, and troubleshooting.…”
Section: A Online Programming Learning Platformmentioning
confidence: 99%
“…Today, OJs are used by many educational institutions to conduct courses related to programming, computing, and software engineering [10], [11]. Many universities have created their own automated program assessment (APA) systems for programming courses to accelerate students' learning [12]- [14]. As a result, a large number of programmingrelated submission logs are created every day by OJ or APA systems in various organizations worldwide, which can be valuable resources for research and analysis [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…Programming skills are developed primarily through repetitive practice, and many universities [2][3][4][5] have created their own programming learning platforms to facilitate such practice by their students. These platforms are often used for programming competitions and serve as automated assessment tools for programming courses [6].…”
Section: Introductionmentioning
confidence: 99%